Biomechanical Analysis of Cervical Artificial Disc Replacement Using Cervical Subtotal Discectomy Prosthesis - Wo, Jin; Lv, Zhenjing; Wang, Jing; Shen, Kui; Zhu, Haoran; Liu, Yang; Huang, Yuen; Sun, Guodong; Li, Zhizhong (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Anterior cervical discectomy and fusion (ACDF) sacrifices segmental mobility, which can lead to the acceleration of adjacent segment degeneration. The challenge has promoted cervical artificial disc replacement (CADR) as a substitute for ACDF. However, CADR has revealed a series of new issues that are not found in ACDF, such as hypermobility, subsidence, and wear phenomenon. This study designed a cervical subtotal discectomy prosthesis (CSDP) consisting of a cervical disc prosthesis structure (CDP structure), cervical vertebra fixation structure (CVF structure), link structure, and locking screw, aiming to facilitate motion control and reduce subsidence. The aim of this study was to assess the biomechanics of the CSDP using finite element (FE) analysis, friction-wear test, and non-human primates implantation study. Study Design: For the FE analysis, based on an intact FE C2-C7 spinal model, a CSDP was implanted at C5-C6 to establish the CSDP FE model and compare it with the Prestige LP prosthesis (Medtronic Sofamor Danek, Minneapolis, MN, United States). The range of motion (ROM), bone-implant interface stress, and facet joint force were calculated under flexion extension, lateral bending, and axial rotation. In addition, CSDP was elevated 1 mm to mimic an improper implantation technique to analyze the biomechanics of CSDP errors in the FE model. Moreover, the friction-wear test was conducted in vitro to research CSDP durability and observe surface wear morphology and total wear volume. Finally, the CSDP was implanted into non-human primates, and its properties were evaluated and verified by radiology. Results: In the FE analysis, the ROM of the CSDP FE model was close to that of the intact FE model in the operative and adjacent segments. In the operative segment, the CSDP error FE model increased ROM in flexion extension, lateral bending, and axial rotation. The maximum stress in the CSDP FE model was similar to that of the intact FE model and was located in the peripheral cortical bone region. The facet joint force changes were minimal in extension, lateral bending, and axial rotation loads in CSDP. In the friction-wear test, after the 150-W movement simulation, both the CVF-link-junction and the CDP-link-junction had slight wear. In the CSDP non-human primate implantation study, no subsidence, dislocation, or loosening was observed. Conclusion: In the FE analysis, the biomechanical parameters of the CSDP FE model were relatively close to those of the intact FE model when compared with the Prestige LP FE model. In terms of CSDP error FE models, we demonstrated that the implantation position influences CSDP performance, such as ROM, bone-implant interface stress, and facet joint force. In addition, we performed a friction-wear test on the CSDP to prove its durability. Finally, CSDP studies with non-human primates have shown that the CSDP is effective.